Design and Evaluation of Mebeverine Hydrochloride Microspheres with Novel Timed Release Polymers - M Pradeep Kumar; G Suryanarayana Murthy; A Sreekanth; BV Ramana; Badithala Siva Sai Kiran (International Journal of Pharma and Bio Sciences, 2022)
: Drugs having the shorter half life are needed to be administered frequently in order to maintain the required therapeutic concentrations. One of the strategies to overcome the frequent administration is by developing the controlled release formulations. Microspheres including the micro particles and microcapsules (having a core of the drug) of 1-1000 μm in diameter are one of the emerging controlled drug delivery systems that can eliminate the frequent drug administration. Hence, in the present study an effort was made to formulate microsphere of Mebeverine HCl by using different delayed-released polymers at different concentrations. Different formulations were prepared using guar gum and glutaraldehyde as delayed release polymers and evaluated for the properties like the effect of polymer concentrations on the microsphere formation, particle size, muco-adhesion etc. Also, the prepared microspheres were evaluated for flow properties along with the drug release rates. From the results, it was observed that higher concentrations of polymer resulted in better microsphere formation compared to low concentrations. Projection Microscopic images of optimized formulation showed that the microspheres have rough surface. In vitro drug release studies showed that the optimized formulation showed 96.26 percent Mebeverine HCl release at the end of 13 hours. Overall, it can be concluded that the preparation of Mebeverine HCl microspheres can eliminate the need for frequent administration thereby providing the better therapeutic compliance compared to the conventional dosage forms.